High temperature sintering and its effect on dimensional and geometrical precision and on microstructure of low alloyed steels. (14th March 2020) - Toledo, D.; Cristofolini, I.; Molinari, A.; Arnhold, V.; Kruzhanov, V.; Vervoort, P.; Dougan, M.; Wimbert, L.; Bonnefoy, V.; Hellein, R.; Weber, H.; Baumgärtner, F.; et al.
ABSTRACT: The effect of high-temperature sintering (1180°C and 1250°C) on the dimensional stability, geometrical precision, density and microstructure of rings made of five different low alloy steels was studied. Density and dimensional shrinkage slightly increase with temperature, but the dimensional and the geometrical precision of parts, do not depend on sintering temperature. Sintering temperature maybe therefore increased up to 1250°C without impairing the dimensional and geometrical precision of the investigated rings. An estimation of the effect of the high sintering temperature on tensile properties is presented, based on the microstructure and on the fraction of the load-bearing section. A significant increase in both tensile strength and tensile ductility may be expected, in particular when the sintering temperature is increased up to 1250°C.